Repressing of SOX6 and SOX9 in Situ Chondrogenic Differentiation of Rat Bone Marrow Stromal Cells - Mohammad Hassan Karimfar; Aliasghar Peyvandi; Mohsen Noorozian; Navid Ahmadi Roozbahani; Reza Mastery Farahani; Maryam Sadat Khoramgah; Hadi Azimi; Ayad Bahadori Monfared; Hojjat-Allah Abbaszadeh (Negah Institute for Scientific Communication, 2015)
Introduction: SOX9 is a transcriptional activator which is necessary for chondrogenesis. SOX6 are closely related to DNA-binding proteins that critically enhance its function. Therefore, to carry out the growth plate chondrocyte differentiation program, SOX9 and SOX6 collaborate genomewide. Chondrocyte differentiation is also known to be promoted by glucocorticoids through unknown molecular mechanisms. Methods: We investigated the effects of asynthetic glucocorticoid, dexamethasone (DEX), on SOX9 gene expression in chondrocytes. Results: SOX9 mRNA was expressed at high levels in these chondrocytes. Treatment with DEX resulted in enhancement of SOX9 mRNA expression. The DEX effect was dose dependent (0·5 nM and 1 nM). Conclusion: RT-PCR analysis revealed that DEX also enhanced the levels of SOX9 expression. It was observed that DEX had enhancing effect only on SOX9 the expression level was low for SOX6. It can thus be concluded that chondrocyte differentiation can be promoted by DEX via SOX9 enhancement.